Home settings are associated with less functional decline among older adults compared to community-care foster homes and skilled nursing facilities in Hawaii - Hua Zan; Yanyan Wu; Yan Luo; John P. Barile; Joshua R. Holmes; Joy Agner (PLoS ONE, 2025)
Medicaid-funded home and community-based services (HCBS) allow older adults with disabilities to avoid long-term institutionalization in nursing homes or hospitals. Past research has shown mixed results on the positive impacts of HCBS. These inconsistent results may stem from studies combining varied HCBS settings, obscuring their differential impacts on older adults’ health and well-being. In Hawaii, HCBS settings primarily include private residences and community care foster homes. There is very little research on adult foster homes, and it remains unclear whether adult foster homes are associated with differential rates of functional decline over time compared to private homes or nursing homes. This research contributes to these literature gaps by comparing functional decline (measured using Hawaii Medicaid level-of-care assessments) across three settings: private homes, adult foster homes, and nursing homes from 2014 to 2021. Among 5,315 dual eligible Medicaid recipients, we found distinct characteristics in initial placement. Individuals placed at home were younger and had lower functional impairment scores compared to individuals in foster homes or nursing homes. To increase comparability despite these differences, we matched older adults (n = 852) on baseline functional status, age, sex, marital status, and race/ethnicity using propensity score matching and performed sensitivity analyses on cognitive status. After matching, linear mixed-effects modeling revealed a notably slower rate of functional decline at home compared to nursing homes or foster homes. Individuals at home had fairly stable functional status (low deterioration) over the eight years. Nursing home residents had the fastest rate of decline, followed closely by individuals in foster homes. These findings of the varying functional outcomes across care settings can inform policymakers, families, and caregivers in selecting effective care options.